PERBEDAAN PENGARUH PROGRAM LATIHAN BERBEBAN DAN PLYOMETRIC TERHADAP PENINGKATAN KIME ATLET KARATE DALAM BERMAIN KATA DITINJAU DARI KEKUAT AN OTOT TUNGKAI (Studi Eksperimen pada Atlet Karate di Unit Kegiatan Mahasiswa Karate INKAI Universitas Negeri Yogyakarta) - Danardono Danardono (Jorpres (Jurnal Olahraga Prestasi), 2016)
This research aims to find out: (1) Difference between the effect of plyometrics and weight  training program on increased kime karate athlete in playing kata, (2) the difference of increased kime karate athlete in playing kata between the athletes with high, medium and low leg muscle strength, (3) the interaction effect between training program with leg muscle strength on increased kime karate athlete in playing kata.This research employed an experimental method with 2 x 3 factorial design. The population of the research in the study were the karate athletes in the Student Activity Unit Karate INKAI of Yogyakarta State University. The sampling technique was purposive random sampling. ANOVA was used to analyzing data, the data analysis prerequisite test was done using the sample normality test (Lilliefors test with a = 0.05%) and variance homogeneity test (Bartlett test with a = 0.05%).Based on the result of the analysis, conclusions are drawn as follows: (1) There was difference between the effect of plyometrics and weight training program on increased kime karate athlete in playing kata.The effect of weight training program is better than the plyometric training program, (2) there was difference of increased kime karate athlete in playing kata between the athletes with high, medium and low leg muscle strength. The effect of increased kime karate athlete in playing kata between the athletes with low leg muscle strength this better than the one with high leg muscle strength, the athletes with high leg muscle strength is better than the one with medium leg muscle 17 strength, (3) there was interaction effect between training program with leg muscle strength on increased kime karate athlete in playing kata. The athletes with low leg muscle strength has according if it is weight training program. The athletes with medium leg muscle strength has according if it is plyometric training program. While the athletes with high leg muscle strength has according if it is weight training program. Keywords: Weight Training, Plyometrics, Leg Muscle Strength, Karate.